+0  
 
+1
130
1
avatar+544 

f(x)=3x-2

g(x)=10/x+2

 

a) express the inverse function f^-1 in the form f^-1(x)

 

b) find gf(x)

simplify your answer

 

winkwinkwink

lynx7  Feb 24, 2018

Best Answer 

 #1
avatar+7155 
+3

a)

f(x)   =   3x - 2       Instead of  " f(x) "  let's say  y .

 

y  =  3x - 2            Now let's solve this equation for  x .

                             Add  2  to both sides.

y + 2  =  3x

                             Divide both sides by  3 .

(y + 2)/3  =  x

                             So the inverse function is....

f-1(x)  =  (x + 2)/3

 

b)   I guess that this means find  (g o f)(x) .

 

(g o f)(x)  =  g( f(x) )

 

(g o f)(x)  =  g( 3x - 2 )

 

(g o f)(x)  =  10/( 3x - 2 ) + 2

hectictar  Feb 24, 2018
 #1
avatar+7155 
+3
Best Answer

a)

f(x)   =   3x - 2       Instead of  " f(x) "  let's say  y .

 

y  =  3x - 2            Now let's solve this equation for  x .

                             Add  2  to both sides.

y + 2  =  3x

                             Divide both sides by  3 .

(y + 2)/3  =  x

                             So the inverse function is....

f-1(x)  =  (x + 2)/3

 

b)   I guess that this means find  (g o f)(x) .

 

(g o f)(x)  =  g( f(x) )

 

(g o f)(x)  =  g( 3x - 2 )

 

(g o f)(x)  =  10/( 3x - 2 ) + 2

hectictar  Feb 24, 2018

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.